The use of desensitizing agent to reduce tooth sensitivity after in office bleaching procedure: Penggunaan desensitizing agent untuk mengurangi sensitivitas gigi pascaprosedur in office bleaching - Aryuni Abd Gaffar,; Aries Chandra Trilaksana (Makassar Dental Journal, 2024)
This case report describes the use of desensitising agent to reduce tooth sensitivity after in office bleaching procedure. A 22-year-old female came to RSGMP Universitas Hasanuddin with a chief complaint of lack of confidence due to yellowish front teeth. In office bleaching treatment was performed using 40% hydrogen peroxide and 3% potassium fluoride applicationto reduce tooth sensitivity after bleaching treatment. Desensitising agent was applied to the labial surface of the bleached teeth for 10 minutes. Sensitivity loss with the use of desensitising agents after bleaching procedures is beneficial because it can increase patient comfort. It is concluded that sensitivity arising after in-office bleaching treatment can be eliminated with the use of desensitising agents.